Is Neutrophil-to-Lymphocyte Ratio a Predictor of Coronary Artery Disease in Western Indians?. (24th July 2017) - Sharma, Kamal; Patel, Alap K.; Shah, Komal H.; Konat, Ashwati
Abstract : Introduction . The current study was designed to evaluate the association of neutrophil-to-lymphocyte ratio (NLR) with coronary artery disease (CAD) presence. We also aimed to propose a suitable cut-off of NLR for diagnosis of CAD in Western Indians. Methods . Total 324 patients undergoing coronary angiography were enrolled and were subdivided into two groups: group 1 (n = 99 ; population without CAD) and group 2 (n = 225 ; population with CAD). Results . The results indicated significant (p < 0.05 ) positive association between elevated levels of WBC, neutrophil, monocyte, NLR, hs-CRP, CPK-MB, and troponin I and disease presence. According to subgroup analysis, the association was more profound in male and older population. Among all the markers NLR showed the strongest predictive potential for CAD with highest odds ratio (1.495; 95% CI: 0.942–2.371;p < 0.048 ). Optimum cut-off of NLR for diagnosis of CAD was 2.13 (AUC-0.823;p < 0.001 ; sensitivity: 83.64%; specificity: 63.46%). Association of NLR with other biochemical markers such as hs-CRP, CPK-MB, and troponin I was also observed in quartile analysis. Conclusion . NLR is a simple indicator that could be effectively used for the diagnosis of CAD with a cut-off of 2.13 in Western Indian population.